The impact of electronic marketing on the effectiveness of the commercial bank’s performance, a case study of the Bank of Agriculture and Rural Development, M’sila Agency - saleh, Zahei; laaraf, Faiza (Journal of Research in Finance and Accounting, 2023)
This study aimed to determine the nature of the impact of electronic marketing on the effectiveness of performance of the Bank of Agriculture and Rural Development in M'sila Agency. This was done by defining the concepts of electronic marketing in banks and the effectiveness performance of commercial banks based on previous studies, to achieve the study's objectives the analytical descirptive approach was used using a questionnaire from that was distributed to a sample of 28 employees selected from the study population of 30 employees. The main findings indicated a positive and significant impact of electronic marketing on the bank's effectiveness. The study also provided recommendations, including updating the bank's website, continuous improvements to the information technology system, and a greater training human resources on providing excellent service from the first time.